The Labor Market Impacts of Universal and Permanent Cash Transfers: Evidence from the Alaska Permanent Fund - Damon Jones; Ioana E. Marinescu (Institute of Labor Economics (IZA), 2018)
What are the effects of universal and permanent cash transfers on the labor market? Since 1982, all Alaskan residents have been entitled to a yearly cash dividend from the Alaska Permanent Fund. Using data from the Current Population Survey and a synthetic control method, we show that the dividend had no effect on employment, and increased part-time work by 1.8 percentage points (17 percent). Although theory and prior empirical research suggests that individual cash transfers decrease household labor supply, we interpret our results as evidence that general equilibrium effects of widespread and permanent transfers tend to offset this effect, at least on the extensive margin. Consistent with this story, we show suggestive evidence that tradable sectors experience employment reductions, while non-tradable sectors do not. Overall, our results suggest that a universal and permanent cash transfer does not significantly decrease aggregate employment.
Keywords: H24; I38; J21; J22; 330; unconditional cash transfer; universal basic income; labor supply; employment